Oral Tranexamic Acid Enhances the Efficacy of Low‐Fluence 1064‐Nm Quality‐Switched Neodymium‐Doped Yttrium Aluminum Garnet Laser Treatment for Melasma in Koreans: A Randomized, Prospective Trial. Issue 3 (26th December 2012) - Shin, Jung U; Park, Jihun; Oh, Sang Ho; Lee, Ju Hee
Abstract : Background: Tranexamic acid (TA) has recently gained in popularity in the treatment of pigmentary disorders. Objective: To evaluate the clinical efficacy and safety of oral TA combined with low‐fluence 1064‐nm quality‐switched neodymium‐doped yttrium aluminum garnet (QSNY) laser for the treatment of melasma. Materials and methods: Forty‐eight patients with melasma were enrolled in the study and subsequently divided into two groups: a combination group and a laser treatment group. All patients were treated with two sessions of low‐fluence QSNY laser, and patients in the combination group took 8 weeks of oral TA. Two blinded dermatologists evaluated patients using the Modified Melasma Area and Severity Index (mMASI) and a clinical improvement scale. Results: Mean mMASI score 4 weeks after the second treatment decreased significantly in both groups from base line. Based on overall clinical improvement, a greater number of patients scored as grade 3 and more in the combination group; no patients were scored as grade 4 in the laser‐alone group. Conclusions: Oral TA may prove a safe and efficient treatment option for melasma in combination with low‐fluence QSNY laser therapy.